2018
DOI: 10.1016/j.aop.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Higher derivative corrections to the entropic force from holography

Abstract: The entropic force has been recently argued to be responsible for dissociation of heavy quarkonia.In this paper, we analyze R 2 corrections and R 4 corrections to the entropic force, respectively. It is shown that for R 2 corrections, increasing λGB (Gauss-Bonnet factor) leads to increasing the entropic force. While for R 4 corrections, increasing λ ('t Hooft coupling) leads to decreasing the entropic force. Also, we discuss how the entropic force changes with the shear viscosity to entropy density ratio, η/s,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…From the entropic point of view, the effective entropic force due to the change in entropy obeys [44][45][46][47][48][49][50][51][52]]…”
Section: Entropy Force Generated By the Horizon Interactionmentioning
confidence: 99%
“…From the entropic point of view, the effective entropic force due to the change in entropy obeys [44][45][46][47][48][49][50][51][52]]…”
Section: Entropy Force Generated By the Horizon Interactionmentioning
confidence: 99%
“…For instance, the ratio of shear viscosity to entropy density [23][24][25][26][27], heavy quark potential [28][29][30], drag force [31][32][33], and jet quenching parameter [34,35] have been discussed under R 4 or R 2 corrections. Other interesting results can be found in [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. To the best of our knowledge, although the calculation of the stopping distance under R 4 corrections was performed by [52], the R 2 corrections on this quantity have never been addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al, calculating for the first time the entropic force associated with the heavy quark pair using the AdS/CFT correspondence [28], showed that the entropy increases with the inter-quark distance and the peak of the entropy depends on the nature of deconfinement and emerges near the transition point. After those, the entropic force was calculated by using this method several times, for example, for a moving [29] and rotating quarkonium [30], a moving dipole in a Yang-Mills like theory [31], for the chemical potential effect [32], R 2 and R 4 corrections [33] and for the effect of deformation parameter [34].…”
Section: Introductionmentioning
confidence: 99%